Strategi Pemerintah Nigeria Dalam Penanganan Tentara Pemberontak Boko Haram (2009-2012) - Nofrialdi Nofrialdi; Muharjono Muharjono (Jurnal Paradigma, 2014)
Constellation of security in the era of globalization has shifted from con ict between states into domestic con icts. The main factoras the cause of domestic con ict is the failure of equitable development, and the political legitimacy of the government is low, and inequality and unfair distribution of the economy. one crisis/uprising is happening in the world is the Boko Haram insurgency in Nigeria